Antidiarrheal Action of Bacillus subtilis CU1 CNCM I-2745 and Lactobacillus plantarum CNCM I-4547 in Mice - Urdaci, Maria C.; Lefevre, Marie; Lafforgue, Guylene; Cartier, Christel; Rodriguez, Bertrand; Fioramonti, Jean (Frontiers in Microbiology, 2018)
Preventive actions of probiotics as antidiarrheal agents are well documented, but their mechanisms are poorly understood. Two selected probiotics, Bacillus subtilis CU1 and Lactobacillus plantarum CNCM I-4547, were tested in mouse experimental models of diarrhea and the possible mechanisms of action were investigated. Diarrhea was induced in mice by oral castor oil administration or by i.v. injection of LPS of Salmonella enteritis. The antidiarrheal drug loperamide was used as control. Fecal water excretion was quantified for two hours and paracellular permeability and electrical parameters of the colon were assessed in Ussing chambers. The expression of colonic exchangers or channels and of Toll-like receptor 4 (TLR4) was assessed by immunohistochemistry. Prophylactic treatment with B. subtilis CU1 or with L. plantarum CNCM I-4547 reduced LPS-induced diarrhea. The reduction of water excretion was in the same range as those induced by loperamide. In the castor oil model, this effect was only observed with B. subtilis CU1. The two probiotic treatments abolished the increase in paracellular permeability induced by LPS, but not by castor oil. However, only L. plantarum CNCM I-4547 treatment decreased the colonic expression of TLR-4. After B. subtilis CU1, colonic expression of cystic fibrosis transmembrane conductance regulator (CFTR) was reduced and that of Na+/H+ exchanger 3 (NHE3) increased. B. subtilis CU1 may increase the capacity of the colon to absorb excess of water in diarrheic conditions by acting on CFTR and NHE3 expression. The two probiotics strains showed an impact on diarrhea through limitation of water excretion that may be driven by distinct mechanisms of involve paracellular permeability or electrolyte transport for L. plantarum CNCM I-2745 and B. subtilis CU1 respectively.